Euphorbiaceae novae vel criticae colombianae, iii (1944)
Croton pungens / Croton leptostachyus / Croton ferrugineus / Croton Holtonis / Croton malacophyllus / Croton dolichostachyus / Croton truxillanus / Croton meridensis / Croton sexmetralis / Plukenetia chaponensis / Sapium verum / Sapium Marmieri.